Iimpact of brand equity on company perfomance: case of Tristar insurance company - Waison, Lancelot (Midlands State University, 2017)
This study is an investigation of the impact of brand equity on company performance a case of Tristar Insurance Company. The company is facing a lot of challenges given the fact that its clientele mainly comprised of corporate customers who are struggling under the current economic conditions. Also competition is intensifying in the industry. Tristar Insurance Company is now turning its focus on individual customers. The study focuses on examining whether the strengthening of Tristar Insurance’s brand equity will improve the performance of the company. The objectives of the study were to identify the relationship between brand awareness and sales volume, to analyse the impact of brand loyalty on market share growth and to investigate the impact of brand associations in creating a competitive advantage. The research was carried out at Tristar Insurance Gweru Branch. The research also reviewed literature focusing on three dimensions of brand equity namely brand awareness, brand loyalty and brand associations. The research used the descriptive research design. The target population was 146.The sample size was 100 and it consisted of 90 customers and 10 employees. Interviews and questionnaires were the data collection methods which were used. Interviews were meant for Tristar Insurance Company employees and questionnaires were for customers. Data was presented on table, pie charts and graphs. It was found in the research that Tristar Insurance Company is not sufficiently investing in the improvement of brand equity. The findings highlighted that Tristar Insurance brand is not being advertised sufficiently. Brand awareness has an effect on customer’s purchase decisions. The brand is also worthy to recommend someone. Also Tristar Insurance customers are highly enjoying brand benefits and brand attributes. This research went on to conclude that there is a relationship between brand awareness and sales revenue. Brand loyalty has an impact on market share growth. Also positive brand associations give the company a competitive advantage. Therefore, Tristar Insurance Company was recommended to invest in promoting its brand awareness, upgrading its customer relationship management system to enhance brand loyalty and to form positive brand associations that give customers a positive perception towards the brand. The research has concluded that Tristar Insurance Company must strengthen its brand equity in order to enhance its performance.